Характеристика особливостей освітньої послуги з погляду маркетингу - Дмитрів, А. Я. (Видавництво Львівської політехніки, 2010)
In this paper education service as an object of marketing is analyzed. Three definitions of educational service in terms of her satisfaction personal, collective and social needs are presented. A description of the main features of the higher educational services as a four-dimension system is made. At the first time peculiarities of the main characteristics of services in the context of higher education services and ways to overcome them are presented schematically. Проаналізовано освітню послугу як об’єкт здійснення маркетингу. Подано визначення освітньої послуги з погляду задоволення нею особистісних, колективних та суспільних потреб. Охарактеризовано головні особливості послуг вищої освіти в чотиривимірній системі. Вперше схематично відображено особливості трактування головних характеристик послуг у контексті послуг вищої освіти та шляхи їх подолання.
Keywords: освітня послуга; маркетинг освітніх послуг; особливості освітньої послуги; вища освіта; ринок освітніх послуг; educational service; marketing; higher educational market; peculiarities of the educational services